(untitled) (Revista Contexto & Educação, 2026)
Digital culture has transformed scientific culture, particularly Science Communication (SC) and its potential for Science Education. This participatory study investigates how Biology undergraduates perceive the inclusion of SC videos in their teaching practices. Evidence was collected through interviews and reveals that future teachers consider SC to be accessible, engaging, and reliable, although they report that its presence in schools is limited and often occurs indirectly or informally. SC videos are mainly used as a complement to curricular content and as classroom entertainment. Among the challenges reported are the lack of technological infrastructure in schools and the limited teaching hours assigned to the subject. The findings highlight the need to strategically integrate SC into teacher education, creating new opportunities to connect Science Education with digital culture.